Evaluación del desempeño laboral de la Empresa Dr. Agro S. A en el Período 2023. - Flores Tivi, Bryan Josué (2024)
In any company, one of the most important factors is the performance of employees, since their performance affects both inside and outside the organization. With this in mind, a project has been launched with the general objective of evaluating the work performance of Dr. Agro S.A. employees. During the year 2023. The evaluation focuses on reviewing the effectiveness and procedures used to distribute tasks, such as the impact on productivity and compliance with company goals. An exhaustive diagnosis of the processes was carried out in three key areas: production, quality control and distribution. This analysis helped understand how these processes are managed and identify areas that could be improved to optimize overall performance. Roles and responsibilities in each area will then be examined to detect any mismatches between what is expected and what is actually being achieved. Additionally, a staff competency assessment was conducted to identify skill gaps that may be affecting performance. Finally, strategies will be created to improve job skills in the different departments of the company, using the load matrix to structure these strategies and ensure that staff skills align with the needs of the company. Mechanisms will be implemented to monitor and verify that the improvements implemented really increase productivity and achievement of goals. This comprehensive approach will seek to not only identify areas for improvement, but also establish a sustainable action plan to ensure continued and effective growth.